Structural Biology and Functional Genomics - Bradbury, Edwin Morton; Pongor, Sándor (Springer Science+Business Media, 1999)
Biomedical research will be revolutionised by the current efforts to sequence the human genome and the genomes of model organisms. Of the newly sequenced genes, 50% code for proteins of unknown functions, while as little as 5% of sequences in mammalian genomes code for proteins. New, genome-wide approaches are needed to draw together the knowledge that is emerging simultaneously in a number of fields of genome research. This volume is a high-level survey of the newly emerging concepts of structural biology and functional genomics for biologists, biochemists and medical researchers interested in genome research. Topics included are chromosome and chromatin organisation, novel DNA and RNA structures, DNA flexibility, supercoiling, prediction of protein functions, strategies for large scale structural analysis, and computer modelling